We're here because you were there : immigration and the end of empire / Ian Sanjay Patel. - Patel, Ian Sanjay (Verso, 2022)
What are the origins of the hostile environment for immigrants in Britain? Drawing on new archival material from the Foreign and Commonwealth Office, Ian Sanjay Patel retells Britain's recent history in an often shocking account of state racism that still resonates today.